The Public Citizen Partnership (PCP) Model for Civil Participation in Public Policies and Suggestions for Improving the Model (Third Sector Social Economic Review, 2025)
Global shifts are also driving changes in public policy planning and implementation methods. In this sense, one of the areas where the most radical changes have been observed is public policy financing. Practices ranging from a statist approach to Public-Private Partnerships (PPPs) and citizen participation have emerged in different periods in the field of public financing. Neoliberal policies, which have been influential over the last 40 years and include PPPs, are currently being criticized in various ways, and governance-focused practices with transparency, participation, and accountability, emphasized by approaches such as New Public Governance (NPG) and New Public Service (NPS), have recently gained traction.This study examines how the Public-Citizen Partnership (PVC) model, based on citizen participation and proposed by Demirdaş (2023a; 2023b), can be developed into an example with potential for implementation in current conditions. In this context, a comparative analysis of New Public Management and the frameworks criticizing it, such as NPG and NPS approaches, was conducted. To develop PVC model, related practices such as state-owned enterprises and PPPs, which emerged in different periods, were also comparatively examined. The points that may strengthen the applicability of the model were analyzed through discussions and evaluations on the capacity to adapt to the relevant legal framework and possible application areas, and recommendations were developed based on existing legal regulations. For the development of the model, on the financial side, it is recommended that crowdfunding with a citizen-oriented framework should be implemented. Additionally, on the administrative side, the Public Enterprise Company model, which can prioritize citizen participation, was also recommended. In future studies, issues such as enriching the application areas of the model, conducting feasibility tests in light of the data, and conducting regulatory impact analyses have the potential to contribute to determining the applicability of the model in the financing of public policies.
Keywords: Financial participation; New Public Service; Crowdfunding; New Public Governance; Public-Citizen Partnership